Clinical and immunological characteristics of HIV/syphilis co-infected patients following long-term antiretroviral treatment - Wu, Yuanni; Lu, Lianfeng; Song, Xiaojing; Liu, Xiaosheng; Yang, Yang; Chen, Ling; Tang, Jia; Han, Yang; Lv, Wei; Cao, Wei; Li, Taisheng (Frontiers in Public Health, 2024)
This study aims to analyze the efficacy of anti-syphilis treatment and the impact of syphilis events on HIV virology and immunology in HIV/syphilis co-infected patients on long-term antiretroviral therapy (ART) and to investigate the incidence and factors of syphilis recurrence/re-infection/serofast state. The insights derived from this investigation can potentially guide strategies for preventing and managing syphilis and AIDS. Methods A retrospective case-control study was conducted at the AIDS clinic of Peking Union Medical College Hospital from January 2003 to December 2022. The study involved 86 HIV/syphilis coinfected patients and 86 HIV mono-infected patients matched based on age, baseline CD4+T cell counts, and viral load. We examined the clinical characteristics of HIV/syphilis co-infected patients, evaluated the efficacy of anti-syphilis treatment, and analyzed the dynamic changes in HIV virology and immunology. The Generalized Estimating Equations (GEE) model investigated the factors associated with HIV/syphilis co-infection and syphilis recurrence/reinfection/serofast state.